Great scientists from a small country in war and peace - Igić Rajko; Škrbić Ranko; Stoisavljević-Šatara Svjetlana (Scripta Medica, 2011)
Great scientific discoveries rarely originate from small and poor countries. The Balkan region, an area with frequent wars and numerous invasions, is not considered an appropriate base for scientific research. Despite such opinions, a number of well educated, curious, wise, and brave minds from Serbia and the former Yugoslavia have been able to make significant scientific contributions. As an example, we briefly outline the lives and achievements of two scientists: Milutin Milanković (1879-1958) and Ivan Đaja (1884-1957). Nikola Tesla (1856-1943), and two Nobel laureates of Yugoslav origin, Leopold Ružička (1887-1976) and Vladimir Prelog (1906-1998), are not included here because their scientific contributions were mainly conducted in the USA or Switzerland. Milanković and Đaja overcame many obstacles, including wars, to contribute significantly to science. Unfortunately, each generation in Serbia and in the former Yugoslavia has been severely disturbed by at least one war. However, some researchers, despite wars and limited resources were able to complete their great scientific projects. Notably, such scientists stayed in the country or returned home as soon as peace returned. However, following the recent civil war that split Yugoslavia, many capable scientists did not return to their prewar homes.